QUALITY ASSESSEMENT OF ANTE-NATAL CARE USING THE METHOD OF LOT QUALITY ASSURANCE SAMPLING - Sh. Salarilak; A. Gashtasb I; A. Nadim (Tehran University of Medical Sciences, 1999)
To determine the coverage rate, timeliness and quality of ante-natal care in rural areas under the coverage of Health Houses in West Azerbaijan province, 30 Health Houses (HH) were randomly selected out of 731 HH in the province. In each HH, using the method of Lot Quality Assurance Sampling (LQAS) 28 women having recently born babies was selected. Data were collected using check-list for facilities, and questionnaires and forms to be completed from the files by interview. The study showed that the method of LQAS is quite effective for evaluation of this service at HH level. The weighted total coverage of ante-natal care was 46.2%. Quality of care was acceptable for 53.9% of mothers. The weighted average of time lines of care was 49.8%. Availability of facilities in delivery of this service was 100%, showing there was no short coming in this respect.